What Pedro could do - Woodard, Christopher (University of Nottingham, 2007)
This paper discusses Bernard Williams's famous case of Jim and the Indians. It contrasts two ways of diagnosing the alleged errors of Act Utilitarianism in considering this case. One approach suggests that Act Utilitarianism fails to appreciate the importance of what Jim does; it fails to understand the significance of Jim's agency. This paper favours an alternative diagnosis, according to which Act Utilitarianism fails to appreciate the importance of what Pedro could do; it fails to understand the significance of Pedro's agency.